Polymorphism of microsatellite dinucleotide loci in parthenogenetic lizards Darevskia unisexualis - Omel’chenko, A. V.; Korchagin, V. I.; Sevast’yanova, G. A.; Tokarskaya, O. N. (Doklady. Biochemistry and biophysics, 2009)
This was the first work to perform a molecular-genetic study of individual loci containing (GT)n microsatellites in clone-breeding (parthenogenetic) lizards Darevskia unisexualis. We revealed and characterized in detail the polymorphic loci and showed that alleles of this locus differ in size and structure of the microsatellite locus. A comparative analysis of ve (GT)n-containing loci revealed correlation between the locus structure and the level of its polymorphism.